NILAI PENDIDIKAN DALAM BUKU CERITA KARYA AVAN FATTHURRAHMAN PADA PROSES KEGIATAN BELAJAR MENGAJAR (KBM) - Nur Afif; Muhammad Fianudin; Asrori Mukhtarom (Universitas Muhammadiyah Tangerang, 2021)
Education is important for human life, moral degradation in the current generation has become a serious thing to be tackled by the world of education, especially Islamic education. One form of overcoming it is by instilling Islamic values in students. The Storybook by Avan Fathurrahman is a book in the form of a collection of stories that contain Islamic educational values, can provide good motivation for students. This study aims to find out: What values of Islamic education material are contained in Avan Fathurrahman's Storybook, and how relevant are the Islamic educational values contained in Avan Fathurrahman's Storybook with the world of education. The author uses the type of research Library Research (Library Research), namely research that collects data and information with the help of various materials contained in the literature. In addition to these methods, the author uses the story method. The values of Islamic education contained in the book collection of great Muslim children's stories by Avan Fathurrahman are: The value of aqidah/faith education, namely (faith in Allah), the value of sharia education/worship, namely (prayer, praying, giving alms, studying), the value of education morals, namely (husnudzhan, help, filial piety to parents, trustworthiness, gratitude, amar ma'ruf, apologizing/forgiving, and honest). The relevance of the values of Islamic education to the practice of Islamic education today is the importance of applying the values of Islamic education in the family environment, school environment, and community environment.